Assessment and analysis of genomic diversity and biomarkers in sabahan indigenous populations / Kee Boon Pin - Kee, Boon Pin (2014)

(untitled)
Ever since the proposal of the recent African origin of modern humans and its various opposing concepts, evolutionary studies have been focusing on the discovery of timelines for such events based on traceable records in archaic remains and contemporary human populations. Although the migration of anatomically modern humans between the 7 major continents in the near 120,000 years has been explained and fit well in the “out of Africa” hypothesis, human movement within these continents remains elusive. Human demic events in Southeast Asia region have also been the heat of debate among researchers. It has been proposed that this region was populated by a recent migration wave from Taiwan about 5,000 years ago, accompanying by the expansion of Austronesian languages into various parts of this region and further into Oceania – known as the “out of Taiwan” model. However, genetic studies in the Southeast Asia have been centred on populations lying along the proposed migratory paths, i.e., southern China, Taiwan, Philippines, Eastern Indonesia, and Near Oceania. The study on population in other parts of this region could shed important information, to complement the proposed model, on the understanding of the historical migration within Southeast Asia and also between other neighboring regions. Sabah, at the northern tip of Borneo Island, is strategically located in the centre of Southeast Asia. In the present study, the aim was to characterize the genetic structure of the 3 major indigenous populations in Sabah, i.e., Kadazan-Dusun, Bajau, and Rungus, and correlate them to the migration patterns in this region. A total of 639 indigenous individuals were recruited and genomic DNA was extracted from the blood/buccal samples. Polymorphisms on the nuclear DNA (VNTRs and InDels) were accessed by direct PCR method. In addition, typing of 15 STR markers on each sample was completed via fragment analysis study. Furthermore, the mitochondrial DNA was examined by the screening of the 9-bp deletion in the region V and the nucleotide ABSTRACT │ IV sequence of the 3 hypervariable regions in the D-loop was determined via sequencing reactions. The genetic data generated was subsequently subjected to statistical and comparative analysis. In an overview, these indigenous populations were shown to have high genetic similarity (AMOVA < 5 %). The Kadazan-Dusun and Rungus populations exhibited a closer relationship compared to the Bajaus. Based on the mitochondrial lineages, different waves/directions of dispersal into the Borneo Island that perhaps shaped the genetic discrepancies of the Bajau with the Kadazan-Dusun and Rungus groups were proposed. The Sabahan Bajau population could have persisted and originated from South Philippines since the earliest entry about 50,000 years ago. There was more interaction found in the Bajau with the surrounding lineages, such as East Asia, Mainland SEA, South Asia, and Oceania, which contributed to their high diversity. The Kadazan-Dusun and Rungus on the other hand, may have arrived in nearer timeframes, possibly following a western route through the Palawan Islands after their exodus from Taiwan some 5,000 to 10,000 years ago.